(untitled) (Research, Society and Development, 2021)
The study aims to demonstrate the presence of pressure injuries and describe nursing care for bedridden patients who suffer from these injuries in a hospitalization unit. This is a qualitative, exploratory study, with a literature review. According to data collected, the bedridden patient is highly prone to develop pressure injuries, which can be caused by several factors, among them, when one of the areas of the body is pressed under some soft or rigid surface, with humidity and lack of blood circulation, however, injuries in general can be preventable. Thus, nursing together with the multidisciplinary team must be prepared to develop, develop and apply strategies in the prevention and treatment of patients, once they are aware of the location of the formation of the lesions, medical diagnosis and care provided, they will result in quality of life to the patient. The prescription and nursing care contribute a lot in the care process, the thorough application of prevention in the formation of pressure injuries, must be followed with specific conducts for each case, as well as with the necessary contribution in the conduct. Thus, the application of the Braden scale and the aggregation of strategies applied in prevention, are essential resources to identify the potential risk of the patient, in the evolution of the treatment effectiveness and in the aggravating factor of these injuries. It is concluded that with all the observances raised and with indications of accurate nursing attention, it is assumed that there is a great possibility that the patient will be able to achieve very soon, to recover from the painful pathological process.